Sistem Pengendalian Internal Pemerintah, Sistem Informasi Manajemen Keuangan Daerah, Good Governance dan Kualitas Laporan Keuangan di Kabupaten Jembrana - Swastika, Ida Bagus Putu Julio; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the effect of government internal control systems, regional financial management information systems and good governance on the quality of regional financial reports. This research was conducted in Jembrana Regency Government. The number of samples taken was 50 employees using a purposive sampling method. Data collection is done through questionnaires and documentation. The analysis technique used is multiple linear regression. Based on the results of the analysis shows that the government's internal control system, regional financial management information systems and good governance have a positive effect on the quality of regional financial reports in Jembrana Regency. This means that the better the government's internal control system, the regional financial management information system and good governance implemented in regional government, the higher the quality of the regional financial reports produced. Keywords: SPIP; SIMDA; Good governance; Quality of Regional Financial Statements.